Allyl sulfide-based visible light-induced dynamically reshaped liquid crystalline elastomer/SWCNT nanocomposites capable of multimode NIR photomechanical actuations. (17th June 2020) - Wu, Zhongying; Cheng, Pin; Zhao, Weiguang; Fang, Jianglin; Xu, Tianchi; Chen, Dongzhong
Abstract : The fully light-driven LCE/SWCNT composite films with exchangeable covalent crosslinks possess reconfigurability and recyclability, enabling shrinking, bending and curling motions. Abstract : Liquid crystalline elastomers (LCEs) combine the ordering character of a liquid crystal and the elasticity of a polymer network. The development of fully light-driven LCE-based soft actuators with good reshapeability and recyclability is in high demand. In this work, we prepared SWCNT/LCE composite films through the introduction of allyl sulfide-based dynamic covalent crosslinks in the LCE matrix and the well-dispersed filler single-walled carbon nanotubes (SWCNTs) with a strong photothermal effect. The SWCNT/LCE composite films were facilely fabricated with reorientation and remouldable capabilities regulated by 405 nm visible light. The monodomain composite films demonstrated multimode actuations of contraction, bending, curling, stretching recovery, and even shape memory driven by 808 nm near-infrared (NIR) light. Moreover, the monodomain spiral ribbon or stretching flat strip and the original polydomain composite film can be readily transformed into each other, and reshaped through easily achievable fabrication conditions. Therefore, the well-prepared SWCNT/LCE composite films with exchangeable covalent crosslinks showed promise as candidates for the development of multimode NIR photomechanical soft actuators with fully light-driven controllability and good remouldability.